Wisdom in Words: Educational Metaphors in Chinese University Commencements - Zhao, Yunshu; Wongthai, Nuntana (Journal of Ecohumanism, 2024)
Commencement speeches at universities are the most important part of the educational activities, with the president’s address carrying a rich array of educational metaphors. To better understand the educational values, concepts and developments of higher education institutions, this study examines 100 graduation speeches delivered by university presidents over the past decade as research material, taking Conceptual Metaphor Theory as the theoretical framework. Employing the Metaphor Identification Procedure (MIP), the analysis identifies 13 prominent source domains of educational metaphors across the speeches. The primary categories include PLANT, CONSTRUCTION, WAR, FAMILY, NATURE, JOURNEY, OBJECT, BODY, ECONOMY, LIGHT, CONTAINER, PLACE, and RELIGION. The quantitative data (tokens, types, resonances) shows that the PLANT metaphor is the most dominant (52.88% resonance), followed by CONSTRUCTION at 18.43% and the WAR at 13.43%. TE further qualitative data showed PLANT metaphor emphasizes the importance of patience, care, and a supportive educational environment, reflecting the deep-rooted agrarian culture and values in China. The CONSTRUCTION metaphor illustrates education as a process of systematically building knowledge, comparing with the goal-oriented and collaborative nature of Chinese educational policies. The WAR metaphor, though less frequently used, underscores the challenges and competitive aspects of education, advocating for resilience and strategic thinking among students. Additionally, the other metaphorical domains that also provide diverse perspectives on education, offering a broader understanding of the complexities within the Chinese educational systems. This study enriches perspectives on educational metaphors in Chinese commencement speeches by revealing how metaphorical language influences educational communication, drawing attention, ensuring effective information transmission and enhancing audience understanding of education elements.